Immunopolarization of CD4+ and CD8+ T cells to Type-1-like is associated with melanocyte loss in human vitiligo. - Wańkowicz-Kalińska, A; van den Wijngaard, R; Tigges, B; Westerhof, W; Ogg, G; Cerundolo, V; Storkus, W; Das, P (2003)
Vitiligo is an autoimmune condition characterized by loss of epidermal melanocytes. High frequencies of melanocyte-reactive cytotoxic T cells in the peripheral blood of vitiligo patients and the observed correlation between perilesional T-cell infiltration and melanocyte loss in situ suggest the important role of cellular autoimmunity in the pathogenesis of this disease. We isolated T cells from both perilesional and nonlesional skin biopsies obtained from five vitiligo patients, then cloned and analyzed their profile of cytokine production after short-term, nonspecific expansion in vitro. Perilesional T-cell clones (TCC) derived from patients with vitiligo exhibited a predominant Type-1-like cytokine secretion profile, whereas the degree of Type-1 polarization in uninvolved skin-derived TCC correlated with the process of microscopically observed melanocyte destruction in situ. Detailed analysis of broad spectrum of cytokines produced by perilesional- and nonlesional-derived CD4+ and CD8+ TCC confirmed polarization toward Type-1-like in both CD4 and CD8 compartments, which paralleled depigmentation process observed locally in the skin. Furthermore, CD8+ TCC derived from two patients also were analyzed for reactivity against autologous melanocytes. The antimelanocyte cytotoxic reactivity was observed among CD8+ TCC isolated from perilesional biopsies of two patients with vitiligo. Finally, in two of five patients, tetramer analysis revealed presence of high frequencies of Mart-1-specific CD8 T cells in T-cell lines derived from perilesional skin. Altogether our data support the role of cellular mechanisms playing a significant part in the destruction of melanocytes in human autoimmune vitiligo.